Study of ultrafine magnetic parameters of Fe 2 O 3 @NdFeO 3 nanocomposites depending on the Nd 2 O 3 dopant concentration - Egizbek , K.; Kadyrzhanov, K.K.; Kozlovskiy, A.L. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
Study of ultrafine magnetic parameters of Fe 2 O 3 @NdFeO 3 nanocomposites depending on the Nd 2 O 3 dopant concentration